Performance Art and New Technologies (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
Technological advances throughout the 20th century have radically transformed the ways of perceiving, building, communicating, and preserving images. Performance is a very clear expression of the hybrid and global cultures these changes have generated. This is an analysis of the way in which the new technologies, especially video, have penetrated into the performance art. If we set off from McLuhan’s premises that technology is an extension of our bodies, we must ask ourselves whether the human body has become obsolete.